Development of a nonlinear sonic boom propagation code - Demiroğlu, Yusuf (Graduate School, 2023)
Civil supersonic flight is still one of the most challenging research topics in the aerospace industry. Since Concorde's last flight in 2003, researchers tried to find efficient solutions to make supersonic flights more affordable and reliable. Meanwhile, with the advance of computational power, computational fluid dynamics (CFD) has been implemented in advanced optimization studies involved in elevating supersonic aircraft design processes with given operational criteria and requirements. However, reducing the cost of a supersonic flight by increasing aerodynamic efficiency is not the only concern in civil supersonic transport. The second most important factor for a supersonic aircraft is the noise produced on land due to the shock waves that propagate through the atmosphere to the ground. This phenomenon is called sonic boom which is addressed in this thesis study. A sonic boom generated by a supersonic aircraft can cause very loud noise on the ground that may exceed 100 decibels. This loudness value is not acceptable due to its effects on people's daily life. Therefore, to enable civil supersonic flight over land, sonic boom loudness must be eliminated or reduced below a certain level. This effort is called sonic boom minimization and there are several methodologies that are provided in this study. Lots of studies for sonic boom minimization utilize optimization algorithms that call sonic boom prediction tools along with the CFD solvers. Therefore, to reduce sonic boom loudness, a sonic boom propagation code that accurately predicts sonic boom loudness is essential for the multidisciplinary design optimization of civil supersonic aircraft. In this regard, a new nonlinear sonic boom prediction code, named ITUBOOM, is developed in-house to be incorporated into our design optimization studies to achieve a low-boom aircraft geometry. ITUBOOM is developed in Python programming language for ease of implementation for design studies. A sonic boom calculation process can be broken down into three main steps; a near-field solution with CFD to generate an initial acoustic signal, atmospheric propagation with acoustics methods, and loudness calculation. Unlike other sonic boom codes, ITUBOOM can also be used to generate a near-field pressure directly from CFD outputs by surface slicing or in-flow signature extraction. Then, it can be used to perform atmospheric propagation by taking into account nonlinear effects such as molecular relaxation and thermoviscous attenuation. Results of ITUBOOM are validated against NASA Langley Research Center's well-known sBOOM code for different conditions on benchmark problems and presented in this thesis in detail.
Doğrusal olmayan sonik patlama yazılımı geliştirilmesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: aeroacoustic; aeroakustik; ticari uçaklar; commercial aircrafts